2019
DOI: 10.1136/neurintsurg-2019-015033
|View full text |Cite
|
Sign up to set email alerts
|

Field triage for endovascular stroke therapy: a population-based comparison

Abstract: BackgroundEndovascular therapy (EVT) for stroke improves outcomes but is time sensitive.ObjectiveTo compare times to treatment and outcomes between patients taken to the closest primary stroke center (PSC) with those triaged in the field to a more distant comprehensive stroke center (CSC).MethodsDuring the study, a portion of our region allowed field triage of patients who met severity criteria to a more distant CSC than the closest PSC. The remaining patients were transported to the closest PSC. We compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Systematic search retrieved 18 studies including 7,017 patients (PRISMA flowchart) ( Figure 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most of the included studies were observational and prospective, only one study was a RCT 15 (Table 1). As a result, quality of studies ranged fair to good, with only one RCT achieving optimal score on risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic search retrieved 18 studies including 7,017 patients (PRISMA flowchart) ( Figure 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most of the included studies were observational and prospective, only one study was a RCT 15 (Table 1). As a result, quality of studies ranged fair to good, with only one RCT achieving optimal score on risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the door in to door out times for patients being transferred should be further evaluated and informed by outcome trends in early presenting patients 15,16 . Recent observational studies have shown that bypassing primary stroke centers for patients with suspected LVO in the field leads to shorter treatment times and better outcomes 17 . Moreover, future research in neuroprotection such as with cooling, vasopressors, or other neuroprotective agents should target early presenting patients with favorable imaging profiles, in whom even small delays may impact functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Increased EVT volumes at qualified centers due to greater availability of treatment, refined stroke systems of care, and expanding treatment indications is expected to increase the probability of being faced with multiple patients with concurrent need for time sensitive treatment 2 4 6 10. Such simultaneous presentations may exceed capacity of a single neurointerventional team and result in a clinically detrimental delay of care.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke treatment has been revolutionized by the advent of endovascular thrombectomy (EVT) as the standard of care for acute ischemic stroke due to large vessel occlusion 1–3. As EVT case volumes at qualified centers increase due to expanding treatment indications and improved systems of care, the probability of multiple patients with large vessel occlusion presenting concurrently for time sensitive treatment is also expected to rise 2 4–11. New strategies are needed to ensure optimal care for these patients while maintaining sensitivity to the ever increasing demand on neurointerventionalists 12 13…”
Section: Introductionmentioning
confidence: 99%